Low-complexity single carrier time domain equalization algorithm - HE Shiwen; GUAN Peiwen; PENG Chengzuo; DENG Xunzhe; AN Zhenyu (Tongxin xuebao)
Due to the constraints of the satellite communication systems, the receiver signal processing was carried out in the time domain, which made traditional channel equalization algorithms face the challenge of high-dimensional matrix inversion. Taking full advantage of the special structure of Toeplitz matrix and the idea of successive interference cancellation, a low-complexity single carrier time domain equalization algorithm was proposed to avoid high-dimensional matrix inversion, by converting the high-dimensional channel equalization system into multiple low-dimensional channel equalization systems and performing channel equalization successively. Simulation results show that compared with the traditional channel equalization algorithms, the proposed algorithm can achieve similar or better performance with lower complexity.